1981
DOI: 10.1007/bf00394979
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis under osmotic stress

Abstract: 1. Photosynthesis of leaf slices, mesophyll protoplasts, and intact chloroplasts of spinach was inhibited in hypertonic sorbitol solutions. Sorbitol could be replaced by other nonpenetrating osmotica such as sucrose or glycinebetaine. As a penetrating solute, ethyleneglycol was also inhibitory, but osmolarities required for inhibition of photosynthesis were considerably higher than in the case of non-penetrating osmotica.-2. With leaf slices and protoplasts, 50% inhibition by sorbitol was usually observed at o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Evaluation of the effects of WD on A pot has come from assessing the response of A to increasing external CO 2 concentration (C a ) and calculated C i . The view that g s determines A, even at substantial WD (70 -60 % RWC or less), rests on studies where removing the epidermis (and thus g s ) or increasing C a overcomes the limiting g s (Kaiser and Heber, 1981;Dietz and Heber, 1983;Kaiser 1984Kaiser , 1987Quick et al, 1992;Tourneux and Peltier, 1995;Cornic, 2000). However, a pattern is apparent (see Table 1, and references therein): these studies used plants grown at low irradiance with WD that developed quickly in no or weak light before measurement.…”
Section: Stomatal Conductance Under Water Deficitmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the effects of WD on A pot has come from assessing the response of A to increasing external CO 2 concentration (C a ) and calculated C i . The view that g s determines A, even at substantial WD (70 -60 % RWC or less), rests on studies where removing the epidermis (and thus g s ) or increasing C a overcomes the limiting g s (Kaiser and Heber, 1981;Dietz and Heber, 1983;Kaiser 1984Kaiser , 1987Quick et al, 1992;Tourneux and Peltier, 1995;Cornic, 2000). However, a pattern is apparent (see Table 1, and references therein): these studies used plants grown at low irradiance with WD that developed quickly in no or weak light before measurement.…”
Section: Stomatal Conductance Under Water Deficitmentioning
confidence: 99%
“…(1) Plants are grown under glasshouse or controlledenvironment conditions, often at low light, and samples of leaf are taken and subjected to WD under no or low light, resulting in rapid stress (Kaiser and Heber, 1981;Dietz and Heber, 1983;Kaiser 1984Kaiser , 1987Renou et al, 1990;Tourneux and Peltier, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies (2,16) of drought on in vivo fluorescence transients from cotton leaves. Indeed fluorescence induction is a difficult but powerful method of determining the functioning of photosynthesis in vivo (for a critical review, see [18]).…”
mentioning
confidence: 99%
“…Kaiser et al . (1981) also found a relatively low quantum requirement of 12 mol absorbed photons per mol O 2 produced by the isolated chloroplasts. Earlier work by Larkum (1968) used chloroplasts extracted by nonaqueous techniques from Beta vulgaris , from the same family (Amaranthaceae) as S. oleracea .…”
Section: Relationship Between the Cl− Requirement For Psii‐oec (Re‐)a...mentioning
confidence: 91%
“…Earlier work found higher (60-100 mol m À3 ) Cl À concentrations in aqueously isolated chloroplasts of S. oleracea (Kaiser et al, 1983;Robinson et al, 1983;Robinson & Downton, 1984;Demmig & Winter, 1986); these higher Cl À concentrations were shown to be a result of interference of chloroplast components with amperometric titration assays of Cl À (Schr€ oppel-Meier & Kaiser, 1987). The methodology of aqueous chloroplast extraction produces chloroplasts with CO 2 -and light-saturated rates on a Chl basis that were at least as high as those found for leaf slices of S. oleracea (Kaiser et al, 1981). Kaiser et al (1981) also found a relatively low quantum requirement of 12 mol absorbed photons per mol O 2 produced by the isolated chloroplasts.…”
Section: Introductionmentioning
confidence: 96%